Meningkatkan Minat Dan Hasil Belajar Matematika Materi Nilai Tempat Melalui Model Pembelajaran Course Review Horay Pada Siswa Kelas II SD 2 Padurenan - Mimik Sugiarti (Journal Prakarsa Paedagogia, 2018)
This research is motivated by the initial conditions of the 2nd grade students of SD 2 Padurenan who have constraints, namely low learning interest, which is only 50%, and the completeness of student learning outcomes is only 36%. So from that step is taken to improve both by applying the Course Review Horay (CRH) learning model, because this model can make students more interested and enthusiastic in learning. After two cycles of research using this CRH model, it was concluded that students' learning interest increased to 86%, and the completeness of student learning outcomes increased to 93%.